The role of immunoglobulin D in autoimmunity.
'Systemic lupus erythematosus' (SLE) is an inflammatory autoimmune disease associated with increased levels of 'immunoglobulin D' (IgD). Understanding the connection between the two will lead to improved therapies for SLE.